Simvastatin Promotes Cardiac Myocyte Relaxation in Association with Phosphorylation of Troponin I - MacDougall, David A.; Pugh, Sara D.; Bassi, Harpreet S.; Lotteau, Sabine; Porter, Karen E.; Calaghan, Sarah (Frontiers in Pharmacology, 2017)
The number of people taking statins is set to increase across the globe due to recent changes in prescription guidelines. For example, half the US population over 40 is now eligible for these drugs, whether they have high serum cholesterol or not. With such development in policy comes a stronger need for understanding statins’ myriad of effects. Surprisingly little is known about possible direct actions of statins on cardiac myocytes, although claims of a direct myocardial toxicity have been made. Here we determine the impact of simvastatin administration (40 mg/kg/day) for 2 weeks in normocholesterolaemic rats on cardiac myocyte contractile function and identify an underlying mechanism. Under basal conditions, statin treatment increased the time to half (t0.5) relaxation without any effect on the magnitude of shortening, or the magnitude/kinetics of the [Ca2+]i transient. Enhanced myocyte lusitropy could be explained by a corresponding increase in phosphorylation of troponin I (TnI) at Ser23,24. Statin treatment increased expression of eNOS and Ser1177 phosphorylated eNOS, decreased expression of the NOS-inhibitory proteins caveolin 1 and 3, and increased (P=0.06) NO metabolites, consistent with enhanced NO production. It is well established that NO stimulates protein kinase G, one of the effectors of TnI phosphorylation at Ser23,24. Trends for parallel changes in phospho-TnI, phospho-eNOS and caveolin 1 expression were seen in atrial muscle from patients taking statins. Our data are consistent with a mechanism whereby chronic statin treatment enhances TnI phosphorylation and myocyte lusitropy through increased NO bioavailability. We see no evidence of impaired function with statin treatment; the changes we document at the level of the cardiac myocyte should facilitate diastolic filling and cardiac performance.